Inovasi Pembuatan Teh Herbal dari Limbah Daun Kopi Robusta sebagai Upaya Pengurangan Sampah dan Peningkatan Kualitas Hidup Masyarakat: Innovation in the Production of Herbal Tea from Robusta Coffee Leaf Waste: A Strategy for Waste Reduction and Enhancement of Community Quality of Life - Santoso, Budi; Parwiyanti, Parwiyanti; Priyanto, Gatot; Wijaya, Agus; Rosidah, Umi; Malahayati, Nura; Yanuariati, Anny; Hermanto, Hermanto; Syafutri, Merynda Indriayani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Coffee farmers typically prune coffee leaves 2-3 times a year to promote healthier and more productive coffee plants; however, this leaf waste negatively impacts the community. This initiative aims to empower local communities by providing training and skills in processing coffee leaf waste into economically valuable herbal tea products. The outcome of this community service activity is herbal tea made from coffee leaves, packaged similarly to commercial tea products. The target community has gained an understanding of the health benefits of this herbal tea, and their skills in producing coffee leaf herbal tea have improved significantly.